2006
DOI: 10.1080/07357900500449553
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Radioimmunotherapy in the Age of Molecular Engineering and Pretargeting

Abstract: Now that radioimmunotherapy is an approved method for the treatment of certain types of non-Hodgkin's lymphoma, investigators are turning to new approaches to further improve radionuclide targeting in hopes of expanding the use of this technology. A number of innovative recombinant proteins have been developed with more favorable pharmacokinetic and targeting properties than standard whole IgG, which conceivably could improve the therapeutic index for cancer treatment. Pretargeting methods also are coming of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…This study is concentrated mainly on the biodistribution aspect. Radioimmunotherapy studies have mainly used IgG as a targeting vector (38). Long circulation time provides high tumor accumulation of slowly extravasating bulky immunoglobulins but, at the same time, causes unacceptably high doses to bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…This study is concentrated mainly on the biodistribution aspect. Radioimmunotherapy studies have mainly used IgG as a targeting vector (38). Long circulation time provides high tumor accumulation of slowly extravasating bulky immunoglobulins but, at the same time, causes unacceptably high doses to bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considerable efforts have been made to re-engineer antibodies to decrease their circulation time and improve their tumor-to-background ratio. 2,17 One common strategy employed is to reduce the immunoglobulin size, which can increase its renal excretion and consequently decrease its time in circulation. Furthermore, decreasing the size of the antibody may also improve tumor penetration and targeting.…”
Section: Pretargeting the Massesmentioning
confidence: 99%
“…Similarly, diagnostic radioisotopes are used to image the expression of cancer-restricted biomarkers in radioimmunodetection applications. 1,2 Although monoclonal antibodies against tumor-associated antigens are often utilized as the delivery vehicles, there can also be other high-affinity ligands, such as peptides or retargeted interleukins that recognize tumor-restricted membrane receptors or antigens. 3 The enormous potential of tumor selective targeting strategies in cancer diagnosis and therapy has led to remarkable advances in the identification of novel cancer-restricted biomarkers, ligand development/optimization, radioisotope selection and nuclear imaging technology.…”
mentioning
confidence: 99%
“…These agents cleared more quickly from the blood and allowed earlier detection without the need for computer manipulation. Radiochemistry advances brought new capabilities to examine conjugates prepared with 111 In and 99m Tc, and clinical studies showed improved disease disclosure or upstaging with these new agents, leading to several product approvals (Goldenberg and Larson, 1992;Goldenberg et al, 1997;Sharkey and Goldenberg, 2006). As imaging agents, they had excellent specificity, but relatively poor sensitivity and image resolution, because the target/noise ratios did not compare well with 18 F-fluorodeoxyglucose (FDG), which replaced most of these first-generation products.…”
mentioning
confidence: 99%